Cyclic performance characterization of a high-temperature thermal energy storage system packed with rock/slag pebbles granules combined with encapsulated phase change materials. (1st February 2023) - ELSihy, ELSaeed Saad; Mokhtar, Omar; Xu, Chao; Du, Xiaoze; Adel, Mohamed
Highlights: Cyclic performance of various hybrid sensible-latent storage structures investigated. Concentric-dispersion model of the rock/slag pebbles-PCM systems developed. Effects of two rock/slag pebbles-PCM volume fractions on cyclic behaviors revealed using hypothetical and average scenarios. The average scenario exhibits the best behavior in terms of capacity and utilization ratios. Slag pebbles show the highest dynamic performance than quartzite rock. Abstract: A thermocline hybrid sensible-latent heat storage system is one of the promising solutions to avoid the challenges encountered by the two storage techniques to what extent and holds the benefits of both methods. Hence, the present study investigates the cyclic performance characteristics of a thermal energy storage system packed with rock/slag pebbles granules combined with encapsulated phase change material (PCM). A concentric-dispersion model is developed to evaluate cyclic behavior based on two different volume fractions. Two different scenarios are adopted for each volume fraction. A hypothetical scenario evaluates the behavior assuming that two PCMs at both tank extremes have the same thermo-physical properties of solid granules in the mid-layer. The average scenario evaluates behavior using the average thermo-physical properties of the three storage materials packed in a tank. The results show that the two adopted strategies greatly influence the system's performance indicators. Based on the hypothetical strategy, the total bed energy stored in cases 2 and 4 is greater than that of the average scenario, resulting in charging 53.8 kWh in case 2 and 54 kWh in case 4. Besides, the system's energy recovered has a peak value of 43.3 kWh in a hypothetical strategy in cases 4 and 1, whereas case 3 has the lowest value of 36.3 kWh in the average scenario. The increased percentages in the capacity ratio of the average scenario than a hypothetical scenario are 5.5 %, 9.84 %, 3.52 %, and 9 % in cases 1, 2, 3, and 4. Moreover, they reach 9.8 %, 16.45 %, 10 %, and 17.55 % in the same cases for the total utilization ratio.